Insights into the complicated networks contribute to adventitious rooting in transgenic MdWOX11 apple microshoots under nitrate treatments. (16th August 2022) - Tahir, Muhammad Mobeen; Tong, Lu; Fan, Li; Liu, Zhimin; Li, Shaohuan; Zhang, Xiaoyun; Li, Ke; Shao, Yun; Zhang, Dong; Mao, Jiangping
Abstract: Adventitious root formation is a bottleneck for the mass propagation of microshoots, and nitrate is an essential nutrient regulating adventitious roots. WOX11 is involved in adventitious rooting. But the crosstalk between nitrate and WOX11 is completely unknown. In this study, MdWOX11 transgenic apple microshoots were grown on different nitrate treatments. Low nitrate promotes adventitious rooting in overexpressed microshoots more than wild type and RNA interference microshoots. In contrast, medium nitrate significantly inhibits it in overexpressed and RNA interference microshoots compared with wild type microshoots. Stem anatomy indicated that medium nitrate delays root primordia formation compared with low nitrate. Methyl jasmonate and zeatin riboside played positive and negative roles in adventitious rooting, respectively. Transcriptomic analysis was conducted to understand the molecular mechanisms behind the phenotypes better. Hormone signalling, sugar metabolism, nitrogen metabolism, cell cycle and root development pathway‐related genes were selected for their potential involvement in adventitious rooting. Results suggest that nitrogen signaling and MdWOX11 expression affect cytokinin accumulation and response to cytokinin through regulating the expression of genes related to cytokinin synthesis and transduction pathways, which ultimately affect adventitious rooting. This study provided important insights into the complicated networks involved in adventitious rooting in transgenic microshoots under nitrate treatments.